2020
DOI: 10.1111/eea.12889
|View full text |Cite
|
Sign up to set email alerts
|

Chemical cues from competitors change the oviposition preference of Drosophila suzukii

Abstract: Although Drosophila suzukii Matsumura (Diptera: Drosophilidae) infests fresh and ripening fruits, it is attracted to fermented fruits as well. Because fermented fruits attract other flies too, if D. suzukii utilizes fermented fruits as oviposition substrates, competition can be more intense on them. To avoid such competition, D. suzukii may change oviposition preference when particular species of competitor flies are present, but the effect of odor cues associated with competitors on the oviposition preference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 37 publications
(49 reference statements)
2
26
0
Order By: Relevance
“…Shaw et al (2018) [ 5 ] observed that groups of D. suzukii females tend to avoid egg laying on an artificial fly culture medium infested with eggs and larvae of heterospecific Drosophila ( D. melanogaster ). In part, similar observations were made by Kidera et al (2020) [ 6 ], who let different Drosophila species oviposit on an artificial fruit medium (grape juice agar) and subsequently allowed groups of D. suzukii females to make their oviposition choice. Here we argue that the use of an artificial substrate and fly groups in confined spaces can be a serious problem for identifying a hierarchical order of oviposition preferences among different potential host fruit categories.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Shaw et al (2018) [ 5 ] observed that groups of D. suzukii females tend to avoid egg laying on an artificial fly culture medium infested with eggs and larvae of heterospecific Drosophila ( D. melanogaster ). In part, similar observations were made by Kidera et al (2020) [ 6 ], who let different Drosophila species oviposit on an artificial fruit medium (grape juice agar) and subsequently allowed groups of D. suzukii females to make their oviposition choice. Here we argue that the use of an artificial substrate and fly groups in confined spaces can be a serious problem for identifying a hierarchical order of oviposition preferences among different potential host fruit categories.…”
Section: Introductionsupporting
confidence: 65%
“…Avoidance of heterospecific cues by the fruit pest Drosophila suzukii is currently discussed as a possible mechanism that reduces interspecific competition with faster developing Drosophila spp. [ 5 , 6 ]. Unlike related Drosophila fruit flies (e.g., D. melanogaster ) D. suzukii possesses a strongly sclerotized ovipositor, with which females can pierce the skin of, and lay eggs into, numerous wild and domesticated fruits [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both D. suzukii and D. melanogaster display yeast-mediated oviposition preference, with yeast being a major attractant, more so than fruit volatiles, for D. melanogaster ( Becher et al. 2012 ), and D. suzukii exhibiting competition dependent yeast attraction, choosing to oviposit in substrates without yeast only when other species are present ( Kidera and Takahashi 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…This lack of behavioral difference despite clear differences in ripe vs. rotten fruit oviposition preference may be due to the key role of yeast, which converts fruit sugars to ethanol during fermentation, in guiding natural oviposition preference. Both D. suzukii and D. melanogaster display yeast-mediated oviposition preference, with yeast being a major attractant, more so than fruit volatiles, for D. melanogaster (Becher et al, 2012), and D. suzukii exhibiting competition dependent yeast attraction, choosing to oviposit in substrates without yeast only when other species are present (Kidera and Takahashi, 2020). Figure 2E, S2D, supplementary file 2).…”
Section: Suzukii Displays a Preference For Stiff Oviposition Substmentioning
confidence: 99%